TO VERIFICATION OF E-LEARNING EDUCATIONAL TEXT IN THE SUBJECT MATEMATICS FOR PHYSICISTS - HORVATHOVA, Daniela (Trends in education, 2008)
In the submitted contribution we are demonstrating the creation of a new E-learning educational programme and our first experience with this implementation. This program was created as a part of the subject called Matematics for Physicists and it is included in the winter term schedules of the first year of teacher-training specializations with physics.
Keywords: E-learning; LMS Moodle; interactive educational text.